Microinvasive esthetic approach for deep enamel white spot lesion - Júlia De Oliveira Farias; Maria Catarina Alves Cunha; Vivian Leite Martins; Paula Mathias (Wolters Kluwer Medknow Publications, 2022)
The white spot lesion on the dental enamel is an optical alteration that compromises the esthetics of smile. It can be caused by many factors, among them, defects in mineralization and formation of tooth enamel. Resin infiltrants are agents that penetrate, by capillarity, through the pores of the demineralized or hypomineralized enamel, altering the refractive index (RI) of the tooth structure and totally or partially masking the appearance of the white spot. The aim of this work was to report the use of resin infiltration to minimize the visualization of white spot lesion, present in an upper central incisor, as a microinvasive approach for the esthetic treatment of deep enamel hypomineralization. A 20-year-old female patient sought care with the esthetic complaint of extensive white spot lesion on the buccal face of her upper right central incisor. The diagnosis established was a deep white stain associated with the incisor molar hypomineralization syndrome, and the treatment of choice for the resolution of the case was the application of the Icon® resin infiltrant (DMG, Hamburg, Germany). To reach the body of the lesion, three cycles of acid erosion, using 15% HCl, were necessary to obtain a satisfactory aspect of masking the white lesion. A camouflage effect of the deep white spot lesion was achieved with the use of the resin infiltration, without the need of additional and irreversible wear of the dental structure.